2008
DOI: 10.2320/matertrans.mra2008091
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ultrasound on Corrosion Behavior of SUS304 Stainless Steel with Crevice

Abstract: Anodic polarization on SUS304 stainless steel with crevice was carried out in 3.5 mass% NaCl aqueous solution. After the anodic current density reached i ¼ 10, 12 or 50 A/m 2 , the potential at that moment was held constantly for a prescribed period. When an ultrasound (US) was applied to the specimen through the solution during the holding period of the potential, the current density on the specimen surface was measured and compared to that without the application of US. As a result, both the pitting corrosio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…This indicates that US suppressed the initiation of pitting corrosion, similar to that observed during the growth stage of pitting corrosion. [14][15][16][17][18][19] This result can be more clearly seen in the measurement of accumulated electric charge during the PH, with the value of 2.8 kC m 22 in the absence of US at i 0 ¼ 0.1 A m 22 being reduced to 1.4 kC m 22 . The accumulated electric charge is an indicator of the dissolution of metal ions into solution during this period.…”
Section: Variations Of Current Density At Pitting Initiation and Grow...mentioning
confidence: 89%
See 1 more Smart Citation
“…This indicates that US suppressed the initiation of pitting corrosion, similar to that observed during the growth stage of pitting corrosion. [14][15][16][17][18][19] This result can be more clearly seen in the measurement of accumulated electric charge during the PH, with the value of 2.8 kC m 22 in the absence of US at i 0 ¼ 0.1 A m 22 being reduced to 1.4 kC m 22 . The accumulated electric charge is an indicator of the dissolution of metal ions into solution during this period.…”
Section: Variations Of Current Density At Pitting Initiation and Grow...mentioning
confidence: 89%
“…8 In addition, the growth of both the pitting corrosion and the crevice corrosion of stainless steel could be suppressed by applying ultrasound (US) in NaCl aqueous solution. [14][15][16][17][18][19] These findings were likely due to the removal of corrosion products on or within the pits and crevices by the microprobe or ultrasonic cavitation, which can diminish the enrichment of Cl 2 and H þ ions in the growing pits or crevices. In the case of pitting corrosion, US was found to remove the metallic covers.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several papers reported that the corrosion on stainless steel can also be suppressed by the application of ultrasound in chloride containing solutions (Nakayama & Sasa, 1976;Whillock & Harvey, 1996;Wang & Nakasa, 2007;Wang & Kido, 2008;Wang, 2008). Nakayama and Sasa measured the polarization curves of a 304 type stainless steel in 0.1 N NaCl solution when applying a 200 kHz and 38-46 kW/m 2 ultrasound with a vibratorto-specimen distance of 60 mm (Nakayama & Sasa, 1976).…”
Section: Corrosion Process Of Stainless Steel With Formation Of Corromentioning
confidence: 99%
“…Whillock et al found that ultrasound www.intechopen.com can encourage the passivation of 304L stainless steel in 2 N HNO 3 containing small amounts of Cl - (Whillock & Harvey, 1996). Wang et al investigated the detail of the suppression effect of ultrasound on stainless steel in chloride solution (Wang & Nakasa, 2007;Wang & Kido, 2008;Wang, 2008;Wang & Kido, 2009;Wang, 2011).…”
Section: Corrosion Process Of Stainless Steel With Formation Of Corromentioning
confidence: 99%